Pengaruh Tarif Pajak, Ketetapan Pengalokasian Pajak dan Keadilan Pajak terhadap Tax Evasion oleh Wajib Pajak Orang Pribadi - Ima Syafi’ah Rahayu; Suhirman Madjid (Majalah Sainstekes, 2018)
One of the income of the country is tax. Tax used to fund welfare and prosperity life masyarakat. The fundamental characteristics tax is force and systems impressed difficult and intractable resulting in the tax disobedient in paying its tax. In general taxpayers seek to make can pay decline possible amout tax or him as much as possible avoid. There are two ways to minimise taxes, the first with tax avoidance and tax evasion. This study aims todo analyze factors affecting tax evasion. As for those factors is the influence tax rate, the accuracy of the allocation of tax and tax equality. Population in this research is taxpayers individual listed on KPP Pratama Bekasi Utara. Sample in this research determined based on a method of convenience of sampling, data collected  by the division of the questionnaire. The method of analysis lab data used is linear regression multiple. Based on the analysis shows taht tax rate have a positive influence and significant impact on tax evasion, the accuracy of the allocation of tax have a negative influence and a significant impact on tax evasion, the tax equality have a negative influence and significant impact on tax evasion.